FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN LAPORAN KEBERLANJUTAN PADA PERUSAHAAN DI INDONESIA TAHUN 2020 – 2024: STUDI LITERATUR REVIEW - Anselmus Rufus Kodu,; Heri, Heri; Rimi Gusliana Mais, (Juremi: Jurnal Riset Ekonomi, 2024)
Disclosure of sustainability reports has become increasingly important in the business and investment world, reflecting a company's commitment to environmental, social, and governance (ESG) aspects. This study aims to analyze the influence of profitability, leverage, company size, and liquidity on sustainability reporting disclosure of companies listed on the Indonesia Stock Exchange (IDX) from 2020-2024. This study collects and synthesizes findings from relevant previous studies through a literature review method. The analysis results show that profitability has a positive effect on disclosure, although there are variations in the results in other studies. Leverage shows a negative relationship, reflecting the focus of highly indebted companies on financial obligations rather than sustainability disclosure. Company size is generally positively related to disclosure, while liquidity does not always show a significant effect. These findings highlight the importance of industry context and unique company characteristics in analyzing sustainability reporting disclosure. This research is expected to provide new insights and recommendations for companies to improve the transparency and accountability of their sustainability reporting.